Market Uncertainty and the Least-Cost Offering Method of Public Utility Debt: A Note - Fabozzi, Frank J.; Moran, Eileen; Ma, Christopher K. (Journal of Finance, 1988)
Frank J. Fabozzi, Eileen Moran, Christopher K. Ma, Market Uncertainty and the Least-Cost Offering Method of Public Utility Debt: A Note, The Journal of Finance, Vol. 43, No. 4 (Sep., 1988), pp. 1025-1034